Opis Varaždinskog generalata (1783.) kao izvor za etnokonfesionalnu povijest - Milković, Kristina; Roksandić, Drago; Fijok, Jasenka (2002)
Opis Varaždinskog generalata iz 1783. godine
Projekt MZOS
HRV-ENG